Splošna leksika in večpodročni termini v govoru turizma - Mikolič, Vesna (Slavia Centralis, 2020)
GENERAL LEXIS AND MULTIDISCIPLINARY TERMINOLOGY IN TOURISM DISCOURSEDrawing upon the Dictionary of Tourism Terminology (TURS) the study shows the specifc traits of tourism lexis, which is characterized by strong terminologization and de-terminologization processes, or rather, by the interaction of the general lexicon and multidisciplinary terminology within the feld of tourism. Lexical entries in the dictionary provide information about the source feld of a term by indicating the type of tourism and a specifc feld indication, the defnition of term, and illustrative examples. Determining the tourism subfelds is especially important with multidisciplinary terms, since their meanings and concepts intertwine differently in various felds.
Keywords: tourism; terminology; terminologization; polysemy; multidisciplinarity; transdisciplinarity